Orientalism, Multiculturalism, and Identity Politics: Hindus and the British caste law - Shah, Prakash (Riflessioni di metodo sul diritto comparato delle religioni, 2017)
This article discusses the role played by British Hindus in contesting legislation against caste discrimination. It gives an account of their limited objections to the law on caste by placing them within the context of British multiculturalism and the constraints that brings. It introduces some considerations concerning the form their objections to the legislation take, and explains their objections in terms of their inability to contest the premises behind the Western construction of Hinduism and of the caste system.